2018
DOI: 10.4314/ijbcs.v12i4.2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different <i>Moringa oleifera</i> extracts and fruit peels on the growth of <i>Solanum scabrum</i>

Abstract: There is a continuous search for natural and safe sources of plant nutrients to replace inorganic fertilizers. Moringa oleifera is one of such alternatives that have been investigated to ascertain its effect on the growth and yield of other crops. Other sources need to be explored. This study investigated the effect of Moringa oleifera extracts and a mixture of orange and banana peels on the growth and vegetable yield of Solanum scabrum Mill, an underutilized, highly nutritious and medicinal leafy vegetable. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Those may be the reasons for increase root length in fruit peel applied okra plants compared with control. It is in line with Sakpere et al (2018) who noted that root length was enhanced by fruit peels treated Solanum scabrum plants than untreated plants. Bakry et al (2016) who stated that banana peel extract significantly increased chlorophyll a, chlorophyll b, total carotenoids and consequently total pigments and maximum increase of the photosynthetic pigments.…”
Section: Root Lengthsupporting
confidence: 91%
See 1 more Smart Citation
“…Those may be the reasons for increase root length in fruit peel applied okra plants compared with control. It is in line with Sakpere et al (2018) who noted that root length was enhanced by fruit peels treated Solanum scabrum plants than untreated plants. Bakry et al (2016) who stated that banana peel extract significantly increased chlorophyll a, chlorophyll b, total carotenoids and consequently total pigments and maximum increase of the photosynthetic pigments.…”
Section: Root Lengthsupporting
confidence: 91%
“…Bakry et al (2016) noted that foliar application of banana peel extract helps to increased root dry weight of quinoa plants compared to the untreated plants. Sakpere et al (2018) noted that root length of Solanum scabrum plants were enhanced by fruit peel treated plants than untreated plants.…”
Section: Dry Weight Of Rootmentioning
confidence: 97%
“…However, for future research, natural products such as honey, coconut water and Moringa oleifera leaf extract (Sakpere et al (2018) confirmed the extract to be effective for stimulating plant growth), which are readily available and more cost effective, should be used as an alternative to Indole butyric acid.…”
Section: Discussionmentioning
confidence: 99%
“…Student t test was performed using origins (Iron / Relais markets and street vendors/ supermarkets) of samples as fixed. The tests were performed at p< 0.05 (Sakpere et al, 2018).…”
Section: Discussionmentioning
confidence: 99%